De Novo Fragment Design for Drug Discovery and Chemical Biology. Issue 50 (21st October 2015) - Rodrigues, Tiago; Reker, Daniel; Welin, Martin; Caldera, Michael; Brunner, Cyrill; Gabernet, Gisela; Schneider, Petra; Walse, Björn; Schneider, Gisbert
Abstract: Automated molecular de novo design led to the discovery of an innovative inhibitor of death‐associated protein kinase 3 (DAPK3). An unprecedented crystal structure of the inactive DAPK3 homodimer shows the fragment‐like hit bound to the ATP pocket. Target prediction software based on machine learning models correctly identified additional macromolecular targets of the computationally designed compound and the structurally related marketed drug azosemide. The study validates computational de novo design as a prime method for generating chemical probes and starting points for drug discovery. Abstract : Automated computational molecular design generated a fragment‐sized inhibitor of death‐associated protein kinase 3, which was confirmed by X‐ray crystallography of the kinase–inhibitor complex. Target prediction software identified additional macromolecular targets of the designed compound and the structurally closely related drug azosemide.